Kinetics and mechanism of MgH2 hydrolysis in MgCl2 solutions. (18th November 2021) - Berezovets, Vasyl; Kytsya, Andriy; Zavaliy, Ihor; Yartys, Volodymyr A.
Abstract: In the present work we systematically studied the hydrolysis of magnesium hydride in MgCl2 aqueous solutions, which was used as a process promotor. The initial hydrolysis rate, the pH of the reaction mixture, and the overall reaction yield are all found to be linearly dependent of the logarithm of MgCl2 concentration. The phase-structural and elemental compositions of the formed precipitates showed that they do not contain chlorine ions and solely consist of Mg(OH)2 . The size of the Mg(OH)2 crystallites increased with increasing content of MgCl2 in the aqueous solution. The best agreement between the observed and modelled hydrolysis kinetics was achieved by applying a pseudo-homogeneous model that describes the process rate as increasing with H + ions concentration. The deposition of Mg(OH)2 which is impermeable to water and blocks the surface of the remaining MgH2 however simultaneously and partially suspends this reaction. We therefore propose a mechanism of MgH2 hydrolysis in the presence of MgCl2 that is based on the comparison of the kinetic dependencies, variations of solutions pH and the structural and elemental analysis data for the solid deposits formed during the interaction. We furthermore define the kinetic model of the process, and the equation that describes the variation in pH of solutions containing chloride salts. Hydrolysis efficiency increased with increased relative MgCl2 amount; the best performance being achieved for the stoichiometric ratio MgH2 +0.7MgCl2 (MgCl2 /MgH2 weight ratio of 12.75/100). This provided a hydrogen yield of 1025 mL (H2 )/g MgH2 . Maximum hydrogen yield peaked at 89% of the theoretical H2 generation capacity, and was achieved within 150 min of hydrolysis start, 35% of hydrogen being released in the first 10 min after start, the hydrogen generation rate being as high as 800 mL min −1 ·g −1 MgH2 . Graphical abstract: Image 1 Highlights: Effective hydrolysis of magnesium hydride by adding magnesium chloride. Influence of magnesium chloride on the kinetics of the hydrolysis reaction and the yield of hydrogen. The effect of magnesium chloride concentration on the passivation layer of magnesium hydroxide. Kinetic model of magnesium hydride hydrolysis reaction in the presence of chloride ion. Determination of optimal concentrations of magnesium chloride.